Dge-lugs-paʼi chos skyoṅ Rgyal-chen Śugs-ldan bkag ʼgog gnaṅ baʼi bkaʼ slob Ma bcos sor bźag - Bstan-ʼdzin-rgya-mtsho, Dalai Lama XIV, 1935- (Brug-gźuṅ Kun-spel Sde-tshan], 1980)
Critical remarks on various recent polemic writings on the protective deity, Rdo-rje-śugs-ldan, and the relations between the various Buddhist traditions in Tibet.